ANALISIS GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Saskia Almarita; Farida Titik Kristanti (AKUNTABILITAS, 2020)
This research aims to determine the effect of the company and good corporate governance on financial distress. The type of data used is secondary data taken from the financial statements of companies, services and investments listed on IDX  2008 - 2018 by using purposive sampling as a research sample research method. Total samples in this study were 75 samples. This study uses a survival analysis method with a cox proportional hazard sub-test. This research produces research results on firm size that have a significant negative impact to the financial distress, while GCG represented by concentration ownership, institutional ownership, foreign ownership, independent commissioners and gender diversity does not significantly impact to the financial distress.